دور القانون في الحد من تلوث المياه في ميناء طرابلس: دراسة تحليلية نقدية ‏في القانون الدولي والقوانين الليبية - بكوش، نفيسة المهدي (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
The environment of the harbour is affected by nature on the one hand, and by the ‎actions of workers and human activities due to deliberate or intentional ‎accidents on the other. Therefore, countries worldwide seek to reduce pollution of the ‎environment, especially at sea; thus, exploitation of resources and ways to ‎benefit from them is a key to solving this issue and avoiding serious problems that ‎may not be solved in many cases. Harbours are considered the number one ports from ‎which the world's goods are stored and distributed, and such activities are a source ‎of pollution because marine carriers contain goods that may consist of dangerous ‎substances such as petrochemicals, petroleum materials or radioactive chemicals. In ‎addition, giant vessels consume a large amount of fuel from which pollutants are‎ produced in liquid and gas form, not to mention solid waste produced by human ‎consumption of the crew of the ship. Other sources of sea pollution are what result ‎from the occurrence of incidents throughout history of the collision of ships that may‎lead to oil spills or contaminants caused by sewage water. It is noticed that the speed ‎of reporting pollution incidents greatly benefits and reduces a large proportion of ‎them. States, governments and local institutions seek to increase efficiency in‎reporting pollutants or accidents, and to increase the speed of response and the ‎enactment of laws and legislation. Many countries and organizations have ‎contributed to studies and research that contribute to solving the problem of pollution ‎in terms of training workers in research and development and the establishment of a ‎mechanism or a line of action to enable members to help each other in the event of ‎contamination in one of the participating member states.